# A(n)=-5+6(n-1).. what’s the 12th term?

A(n)=-5+6(n-1).. what’s the 12th term?

## This Post Has 6 Comments

1. trea56 says:

61

Step-by-step explanation:

A(n)=-5+6(n-1)

Let n = 12

a(12) = -5 + 6(12-1)

-5+6(11)

-5+66

61

2. letsgetcookingblog says:

Step-by-step explanation:

According to the question a(n) = -5 for all real values of n.

So the 12th term in the sequence is -5.

3. kaleaweeks says:

Step-by-step explanation:

To find each n term replace the n with term u need to find .

A(12)= -5+6(12-1)

=-5+6(11)

=61

4. kamber3728 says:

Step-by-step explanation:

The 12th term is gotten by replacing ń in the equation with 12. Hence,

a(12)= - 5+6(12-1)

Solving the bracket first by BODMAS,

a12= - 5+6(11)

Opening the bracket,

a12=-5+66

a12=66-5

a12=61

5. versaceblooper says:

61

Step-by-step explanation:

Substitute n = 12 into the given formula, that is

a(12) = - 5 + 6(12 - 1) = - 5 + (6 × 11) = - 5 + 66 = 61

6. sketchers says:

61

Step-by-step explanation:

Put 12 where n is, then do the arithmetic.

a(12) = -5 +6(12-1) = 61

We assume you didn't really mean to show an equation for -a(n). If you did, then the term you want is -61.